Hello, universe - Kelly, Erin Entrada (Greenwillow Books, 2020)
When Chet "the Bull" Bullens pulls an unthinkable prank on shy, misunderstood Virgil, which also affects Gulliver--Virgil's pet hamster--Valencia Somerset and Kaori Tanaka find their lives and Virgil's and Chet's colliding in surprising ways.